Effectiveness of Centella Asiatica and Aloe Vera Gels on Postpartum Stretch Mark Reduction - Arinall Haq; Indria Nuraini; Yuni Khoirul Waroh (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
Stretch marks (striae distensae) are common in postpartum women, caused by excessive skin stretching and dermal tearing. Herbal treatments such as Centella asiatica and Aloe vera are known for their skin-regenerating properties. This study aimed to compare the effectiveness of Centella asiatica gel and Aloe vera gel in reducing stretch marks in postpartum mothers. A quasi-experimental pretest-posttest two-group design was used, data were collected from December 2024 to April 2025 at BPM Sumirah, Surabaya involving 32 postpartum women aged 20-35 years, selected via purposive sampling. The participants were divided into two groups: one received Centella asiatica gel, and the other received Aloe vera gel, applied twice daily for 8 weeks. The Revised Striae Severity Scale (RSSS) assess the severity of stretch marks before and after treatment. Data analysis included paired t-tests and independent t-tests. Results showed significant reductions in RSSS scores for both groups (p = 0.001). The Centella asiatica group decreased from 1.50 ± 0.52 to 0.63 ± 0.50, while the Aloe vera group decreased from 2.50 ± 0.53 to 2.06 ± 0.44. The independent t-test indicated a significant difference (p = 0.001), favoring Centella asiatica gel. In conclusion, Centella asiatica gel is more effective than Aloe vera gel in reducing postpartum stretch marks, suggesting its potential as a natural alternative for improving skin elasticity.